2017
DOI: 10.1021/acs.est.6b03185
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir Water-Level Drawdowns Accelerate and Amplify Methane Emission

Abstract: Water-level fluctuations due to reservoir management could substantially affect the timing and magnitude of reservoir methane (CH) fluxes to the atmosphere. However, effects of such fluctuations on CH emissions have received limited attention. Here we examine CH emission dynamics in six Pacific Northwest U.S. reservoirs of varying trophic status, morphometry, and management regimes. In these systems, we show that water-level drawdowns can, at least temporarily, greatly increase per-area reservoir CH fluxes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
131
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(145 citation statements)
references
References 56 publications
12
131
2
Order By: Relevance
“…Even though ebullition was observed at certain times throughout the experimental time in both groups, our findings do not take into account the contribution of this CH 4 release pathway, which tends to increase in intensity when the water column lowers [51]. Moreover, possible incomplete carbon mineralization not resulting in CO 2 or CH 4 production but in dissolved organic carbon production, is not captured by our analyses.…”
Section: Plos Onementioning
confidence: 58%
“…Even though ebullition was observed at certain times throughout the experimental time in both groups, our findings do not take into account the contribution of this CH 4 release pathway, which tends to increase in intensity when the water column lowers [51]. Moreover, possible incomplete carbon mineralization not resulting in CO 2 or CH 4 production but in dissolved organic carbon production, is not captured by our analyses.…”
Section: Plos Onementioning
confidence: 58%
“…Our own experiences with bubble traps with continuous volume measurements (Horn et al, ) have indicated that exchange was small. Gas loss from control traps has also been shown to be negligible in a study about CH 4 ebullition in a reservoir (Harrison et al, ). Diffusive fluxes depended on the difference of partial pressure of oxygen in the gas phase and the water.…”
Section: Resultsmentioning
confidence: 99%
“…While not an exhaustive list, these management techniques highlight the extent to which human activities may mask or amplify climate signals. For example, within-system management strategies can interfere with biological life cycles (e.g., fish stranding mortality associated with hydropower peaking, Bell et al 2008; and elimination of cyanobacteria blooms via chemical treatments, Jančula and Mar s alek 2011), seasonal hydrologic dynamics (e.g., via pool drawdowns, Zohary and Ostrovsky 2011; and via the reduced evaporation associated with coverings, Alvarez et al 2006), and water column chemistry (reduced water column phosphorus concentrations associated with alum treatments, Kennedy and Cooke 1982;Nogaro et al 2013; and higher concentrations of reduced solutes associated with pool drawdown, Baldwin et al 2008;Zohary and Ostrovsky 2011;Harrison et al 2017).…”
Section: Differences In Waterbody Characteristicsmentioning
confidence: 99%